Aplikasi Bioteknologi untuk Pengolahan Tandan Kelapa Sawit dan Sampah Organik Menuju Kemandirian Pupuk di Desa Kampung Tengah, Siak - Isda, Mayta Novaliza; Fitmawati; Sujarwati; Titrawani; Lestari, Wahyu; Afrilliani, Aneka; Yovita, Cici; Stefani, Dea; Indriani, Desi; Sari, Dwi Retno; Sari, Fajrika; Zulva, Naya Septia; Fahira, Nidia; Ramadhan, Wahyu; Sirait, Yudhistio Artia Perdamaian (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2024)
Empty oil palm bunches (OPEFB) contain important nutrients such as nitrogen (N), phosphorus (P), potassium (K), and micronutrients such as boron (B), copper (Cu), zinc (Zn), iron (Fe), and manganese (Mn). These nutrients can be released into the soil and are available for plant growth with empty oil palm bunches. Composting is a natural recycling method and returns organic matter to the biological cycle. OPEFB as an organic fertilizer has great potential to help increase soil fertility and productivity. Utilization of organic waste in the form of liquid compost can be done using a composter. Processing waste into compost can have quite high economic value. This community service activity received a positive response from the Kampung Tengah village community because it increased knowledge related to the processing of OPEFB waste and also organic waste so that it becomes useful and economically valuable compost.